Nephron-sparing surgery in nonsyndromic unilateral wilms' tumor: An insight into the ongoing surgical controversy - Yogesh Kumar Sarin (Wolters Kluwer Medknow Publications, 2022)
Background: Unilateral Wilms' tumor (uWT) is the most common renal malignancy in the pediatric population. Although the onset of surgical intervention like radical nephrectomy (RN) has substantially reduced the mortality rate, recent evidence has raised concerns regarding several postoperative complications associated with this procedure. Nephron-sparing surgery (NSS) has been reported to avoid such postoperative complications and have high technical success rate. However, not much literature is available comparing the efficacy of RN and NSS for managing nonsyndromic uWT, which makes it less acceptable globally. Materials and Methods and Results: A systematic identification of the literature was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines on four academic databases: MEDLINE, Scopus, EMBASE, and CENTRAL. Out of 1017 records, 20 manuscripts including 312 patients were included in the review; 4 patients treated by the author (unpublished data) have also been included. The studies included 7 retrospective case series with no comparison group, 4 retrospective case series with comparison group, 4 retrospective series with a cursory mention of NSS in uWT, 2 case reports, 1 protocolized prospective trial with comparison group, 1 administrative database analysis with comparison group, and 1 randomized controlled study. In all, 316 patients with nonsyndromic uWT were studied. The pretherapy volumes of the WT ranged from 2.4 to 640 ml. Majority of them were administered preoperative chemotherapy. About half of the patients (n = 159) (50.3%) were Stage I tumors. Stage II, III, and IV tumors were seen in 23 (7.3%), 20 (6.3%), and 3 (1%) patients. Stage was not specified in 111 (35.1%) patients. Majority of them were "intermediate risk" WT. All these tumors were nonanaplastic. Surgical margins were reported positive in 13 (4%) patients. Overall and event-free survivals were 100% in most of the studies; only handful of relapses were noted in this systematic review. Conclusions: This qualitative systematic review recommends the use of NSS for nonsyndromic uWT. The procedure accounts for higher postoperative renal function and lesser incidence of hypertension as compared to the radical nephrectomy. Overall and event-free survivals are comparable or even better with NSS.